THE USE OF GAMES AND PICTURES AS A TECHNIQUE OF TEACHING VOCABULARY: THE CASE OF THE FIFTH YEAR STUDENTS OF SDK KANISIUS JATINGALEH SEMARANG IN TH EACADEMIC YEAR OF 2010/2011 - M. Wahyu Widiyanto; Maria Yustina Rensi Dartani (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2011)
The purpose of this study was to investigate the contribution of games for improving vocabulary acquisition of the Catholic Elementary School of Kanisius Jatingaleh, compared to pictures for improving the same subjects of study. Participants were divided into two treatments groups, and each group was assigned to do the same test, containing sections which involved vocabulary items. Pre-test was given before the experiment and post-test was held immediately after the experiment was over. The Null hypothesis of no significant differences were constructed and tested, and then one-tailed t-test was used to compare the score of the games and pictures groups and to analyze the hypothesis. The results indicated that the score of the experimental group that it was taught by using games is higher than control group. It was proved that the students did better in mastering their vocabulary when they were taught by using games rather than pictures. Both of games and pictures contribute in that way : to help the students develop their inner self, to motivate the students to know more about the new vocabulary, to train the students in creative freedom as they feel less embarrassed or afraid and become more self confident, and to give a challenge to solve problem in enjoyable situation. ?é?á Key Words: Vocabulary Acquisition, Pictures, Games